Bactericidal/Permeability-Increasing Protein Preeminently Mediates Clearance of Pseudomonas aeruginosa In Vivo via CD18-Dependent Phagocytosis - Theprungsirikul, Jomkuan; Skopelja-Gardner, Sladjana; Burns, Ashley S.; Wierzbicki, Rachel M.; Rigby, William F. C. (Frontiers in Immunology, 2021)
Chronic Pseudomonas aeruginosa infection mysteriously occurs in the airways of patients with cystic fibrosis (CF), bronchiectasis (BE), and chronic obstructive pulmonary disease (COPD) in the absence of neutrophil dysfunction or neutropenia and is strongly associated with autoimmunity to bactericidal permeability-increasing protein (BPI). Here, we define a critical role for BPI in in vivo immunity against P. aeruginosa. Wild type and BPI-deficient (Bpi-/-) mice were infected with P. aeruginosa, and bacterial clearance, cell infiltrates, cytokine production, and in vivo phagocytosis were quantified. Bpi-/- mice exhibited a decreased ability to clear P. aeruginosa in vivo in concert with increased neutrophil counts and cytokine release. Bpi-/- neutrophils displayed decreased phagocytosis that was corrected by exogenous BPI in vitro. Exogenous BPI also enhanced clearance of P. aeruginosa in Bpi-/- mice in vivo by increasing P. aeruginosa uptake by neutrophils in a CD18-dependent manner. These data indicate that BPI plays an essential role in innate immunity against P. aeruginosa through its opsonic activity and suggest that perturbations in BPI levels or function may contribute to chronic lung infection with P. aeruginosa.